Microwave-assisted Phospha-Michael addition reactions in the 13α-oestrone series and in vitro antiproliferative properties - Erzsébet Mernyák; Sándor Bartha; Lili Kóczán; Rebeka Jójárt; Vivien Resch; Gábor Paragi; Máté Vágvölgyi; Attila Hunyadi; Bella Bruszel; István Zupkó; Renáta Minorics (Journal of Enzyme Inhibition and Medicinal Chemistry, 2021)
Microwave-assisted phospha-Michael addition reactions were carried out in the 13α-oestrone series. The exocyclic 16-methylene-17-ketones as α,β-unsaturated ketones were reacted with secondary phosphine oxides as nucleophilic partners. The addition reactions furnished the two tertiary phosphine oxide diastereomers in high yields. The main product was the 16α-isomer. The antiproliferative activities of the newly synthesised organophosphorus compounds against a panel of nine human cancer cell lines were investigated by means of MTT assays. The most potent compound, the diphenylphosphine oxide derivative in the 3-O-methyl-13α-oestrone series (9), exerted selective cell growth-inhibitory activity against UPCI-SCC-131 and T47D cell lines with low micromolar IC50 values. Moreover, it displayed good tumour selectivity property determined against non-cancerous mouse fibroblast cells.